(untitled) (Heritage, 2021)
One of the central issues of the modern age is related to the prevention of excessive use of narcotics, but also the Internet and electronic devices in the everyday life of young people. This leads them to loneliness, distance from society, family, people, nature… In order to prevent these problems of the modern age, it is necessary to continuously look for solutions. Some of them are related to youth engagement programs through sports activities outside the regular curriculum. The aim of this paper is to alert the public, especially the intellectual ones, to the necessity of including this type of extracurricular activities in the development of young people’s personalities. The results of the research provide an overview of sports activities that should first be introduced into the plan of extracurricular activities, and which will introduce young people to a healthy growing up, and contribute to their physical and intellectual progress. The paper seeks to point once again to the population as a significant driving force in the development of economies, sports as a significant export branch, a powerful weapon against addiction, and a means of combating crime.